A study of H. pylori infection as risk factor for the gall stone disease - kosma, Vijayalaxmi; Gole, S. N.; Nirala, S. L.; Siddiqui, Rabia Parveen; Agrawal, Sujan Narayan (International Surgery Journal, 2023)
Background: Gallstones are one of the widely occurring digestive/hepatobiliary disorders. Chronic cholecystitis, cholelithiasis or symptomatic gallbladder is a prolonged mechanical or functional disorder of abnormal gallbladder emptying. Nearly eighty percent of the gallstones are cholesterol gallstones, and 20% are pigmented stones consisting of bilirubin and calcium, the two components present in the bile. The diagnosis is established by a variety of diagnostic tools like ultrasonography, CT scan, ERCP, liver function tests and pancreatic enzyme studies. The hypothesis of the presence of H. pylori in the biliary epithelium of the patients with hepatobiliary ailments has been sporadically investigated. Helicobacter pylori (H. pylori) is a spiral, microaerophilic, gram-negative bacterium. There are many suggestive evidences that the DNA components of H. pylori is found in the bile, gallbladder tissue and/or cholesterol gallstones. The association of gallstones with Helicobacter pylori has been investigated by many authors, but not clearly established. Methods: The present study is aimed to identify the Helicobacter pylori infection as a risk factor for gallstone disease. The histopathological samples of gall bladder mucosa were examined by staining with modified giemsa stain, haematoxylin, and eosin. Results: Our study showed the presence of H. pylori in only one case which is not statistically significant. Moreover, the present study was based on H and E stains only and they should have been substantiated with immunohistochemistry and PCR studies. Thus, further studies are required to establish a causal relationship between the Helicobactor pylori infection and gallstone formation. Conclusions: Helicobacter pylori as a risk factor for gallstones is yet to be proven.